Formerly eclamptic women have lower nonpregnant blood pressure compared with formerly pre‐eclamptic women: a retrospective cohort study. (9th March 2015) - Schreurs, MP; Cipolla, MJ; Al‐Nasiry, S; Peeters, LLH; Spaanderman, MEA
<x xml:space="preserve">Abstract</x> Objective To compare nonpregnant blood pressure and circulating metabolic factors between formerly pre‐eclamptic women who did and did not deteriorate to eclampsia. Design Retrospective observational cohort study. Setting Tertiary referral centre. Population Formerly pre‐eclamptic women with (n = 88) and without (n = 698) superimposed eclampsia. Methods Women who experienced pre‐eclampsia with or without superimposed eclampsia during their pregnancy or puerperium were tested for possible underlying cardiovascular risk factors at least 6 months postpartum. We measured blood pressure and determined cardiovascular and metabolic risk markers in a fasting blood sample. Groups were compared using Mann–Whitney U test, Spearman's Rho test or Fisher's Exact test (odds ratios). Main outcome measures Differences in postpartum blood pressures and features of the metabolic syndrome between formerly pre‐eclamptic and formerly eclamptic women. Results Formerly pre‐eclamptic women who developed eclampsia differed from their counterparts without eclampsia by a lower blood pressure (P < 0.01) with blood pressure correlating inversely with the likelihood of having experienced eclampsia (P < 0.001). In addition, formerly eclamptic women had higher circulating C‐reactive protein levels than formerly pre‐eclamptic women (P < 0.05). All other circulating metabolic factors were comparable. Finally, 40% of all eclamptic cases occurred in the puerperium. Conclusions Formerly pre‐eclamptic women with superimposed eclampsia have lower nonpregnant blood pressure compared with their counterparts without neurological sequelae with blood pressure negatively correlated to the occurrence of eclampsia. As about 40% of all eclamptic cases occur postpartum, routine blood pressure monitoring postpartum should be intensified. Tweetable abstract Nonpregnant blood pressure of formerly pre‐eclamptic women is negatively correlated to the occurrence of eclampsia.